2015
DOI: 10.1371/journal.pone.0128651
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Immune Response, Axonal Dysfunction and Reduced Endocytosis in the Substantia Nigra in Early Stage Parkinson’s Disease

Abstract: Subjects with incidental Lewy body disease (iLBD) may represent the premotor stage of Parkinson’s disease (PD). To elucidate molecular mechanisms underlying neuronal dysfunction and alpha-synuclein pathology in the premotor phase of PD, we investigated the transcriptome of the substantia nigra (SN) of well-characterized iLBD, PD donors and age-matched controls with Braak alpha-synuclein stage ranging from 0–6. In Braak alpha-synuclein stages 1 and 2, we observed deregulation of pathways linked to axonal degene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
123
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(127 citation statements)
references
References 58 publications
3
123
0
1
Order By: Relevance
“…This observation is similar to those made in another transgenic α-syn model [67], and indicates that the earliest response to the transgenic abnormal α-syn challenge is at the gene expression level. Interestingly, Dijkstra et al [22] reported a lower number of DEGs in SN from patients late Braak stages (3 and up) compared to patients at an early Braak stage (1)(2). Similarly, in another study, more altered pathways were observed in incidental Lewy Body Disease compared to PD [80].…”
Section: Key Observations In the Transcriptional Profiling Of The Bacmentioning
confidence: 88%
“…This observation is similar to those made in another transgenic α-syn model [67], and indicates that the earliest response to the transgenic abnormal α-syn challenge is at the gene expression level. Interestingly, Dijkstra et al [22] reported a lower number of DEGs in SN from patients late Braak stages (3 and up) compared to patients at an early Braak stage (1)(2). Similarly, in another study, more altered pathways were observed in incidental Lewy Body Disease compared to PD [80].…”
Section: Key Observations In the Transcriptional Profiling Of The Bacmentioning
confidence: 88%
“…Recognition of an important role of neuroinflammation in human PD and in the α-syn PFF model has been growing. 66,[87][88][89][90][91][92][93][94][95] In addition, previous results demonstrated that dieldrin exposure exacerbates MPTP-induced increases in expression of glial fibrillary acidic protein (GFAP) levels in the striatum, suggesting that dieldrin exposure leads to a greater neuroinflammatory response to a second insult. While we were unable to test expression of neuroinflammatory genes after the application of PFFs, we did identify dieldrin-induced changes in the expression of neuroinflammatory genes.…”
Section: Dieldrin Induced Sex-specific Effects In the Nigrostriatal Pmentioning
confidence: 99%
“…On the other hand, transcriptomic changes between PD and non-neurological controls of selected brain regions, e.g. the substantia nigra, have identified several molecular mechanisms underlying PD pathology, including synaptic vesicle endocytosis 911 . However, post-mortem human brain tissue of well-characterized PD patients and controls is scarce, usually focuses on a select number of brain regions, and have a limited coverage of patients with different Braak LB stages, resulting in low concordance of findings across different studies 12 .…”
Section: Introductionmentioning
confidence: 99%
“…We validated the relevance of the identified BRGs to PD progression with two datasets of non-neurological controls (Genotype-Tissue Expression project (GTEx) 19 and UK Brain Expression Consortium (UKBEC) 20 ) and two datasets of PD donors. We found altered expression patterns in patients with PD and incidental Lewy body disease (iLBD), who are assumed to represent the pre-clinical stage of PD 11,21 . In non-neurological brains from the AHBA, we further identified modules of co-expressed genes across Braak LB stage involved regions, and characterized them functionally by assessing their enrichment for cell-type markers, gene ontology (GO)-terms, and disease-associated genes.…”
Section: Introductionmentioning
confidence: 99%